Adverse childhood experiences influence white matter microstructure in patients with schizophrenia. Issue 1 (30th October 2015) - Poletti, Sara; Mazza, Elena; Bollettini, Irene; Locatelli, Clara; Cavallaro, Roberto; Smeraldi, Enrico; Benedetti, Francesco
Abstract: Integrity of brain white matter (WM) tracts in adulthood could be detrimentally affected by exposure to adverse childhood experiences (ACE). Changes of diffusion tensor imaging (DTI) measures suggesting WM disruption have been reported in patients with schizophrenia together with a history of childhood maltreatment. We therefore hypothesized that ACE could be associated with altered DTI measures of WM integrity in patients with schizophrenia. We tested this hypothesis in 83 schizophrenia patients using whole brain tract-based spatial statistics in the WM skeleton with threshold-free cluster enhancement of DTI measures of WM microstructure: axial, radial, and mean diffusivity (MD), and fractional anisotropy (FA). We observed an inverse correlation between severity of ACE and DTI measures of FA, and a positive correlation with MD in several WM tracts including corona radiata, thalamic radiations, corpus callosum, cingulum bundle, superior longitudinal fasciculus, inferior fronto-occipital fasciculus, uncinate fasciculus. Lower FA and higher MD are indexes of a reduction in fibre coherence and integrity. The association of ACE to reduced FA and increased MD in key WM tracts contributing to the functional integrity of the brain suggests that ACE might contribute to the pathophysiology of schizophrenia through a detrimental action on structural connectivity in critical cortico-limbic networks. Highlights: Adverse childhood experiences (ACE) influence white matter integrity. Higher ACE associate with reduced fractional anisotropy. Higher ACE associate with higher mean diffusivity. ACE might contribute to schizophrenia acting on structural connectivity.